Systematic Literature Review Cash Waqf - Hayatul Millah; Abdul Komar (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
The Islamic economy in Indonesia has shown significant growth as public awareness of Sharia-based financial instruments, including cash waqf, has strategic potential to support the social and economic development of the community. Although the potential for cash waqf in Indonesia is estimated to reach trillions of rupiah annually, its management remains far from optimal due to low public literacy, the institutional capacity of nadzir (managers), and weak transparency and innovation in productive waqf management. This study aims to analyze scientific developments, intellectual structures, and key research themes on cash waqf through a Systematic Literature Review (SLR) approach and bibliometric analysis. Data were obtained from the Scopus database using keywords related to cash waqf and Islamic social finance. The analysis shows that the study of cash waqf has evolved towards a multidisciplinary approach emphasizing three main focuses: strengthening the governance and accountability of waqf institutions, innovation in financial instruments such as cash waqf linked sukuk, and behavioral factors and public trust in waqf management institutions. This study confirms that the synergy between good governance, Sharia financial innovation, and increased public literacy and trust is key to optimizing productive and sustainable cash waqf management. These findings are expected to provide conceptual contributions and strategic recommendations for the development of a professional, safe, and Sharia-compliant cash waqf ecosystem in Indonesian.